Rai rai rai. 3 - Yoshiaki (Manga author) (Shōnen Sandē komikkusu., 2026)
Implanted with an extraterrestrial entity, a former space pest exterminator battles deadly alien threats--all to pay her bills! Humanity might've triumphed over the aliens, but that didn't stop struggling space vermin exterminator Sumire Ichigaya from getting abducted by a UFO. After being implanted with a foul-mouthed extraterrestrial entity, she's got a lot more to worry about than just paying her bills. When Duskin is asked to take part in the merciless testing of Sumire's abilities, a sudden attack of conscience pits him against Kiyoharu in a seemingly unwinnable battle, but when the clash between the clearly-not-just-an-accountant and the varmint is interrupted by the arrival of a deadly new enemy with her own devastating powers, Sumire must discover whether she has the strength she needs to fight back.--